2016
DOI: 10.1021/acs.est.6b02286
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Disposal of Arsenic-Bearing Wastes Results in Low Microbially Mediated Arsenic Volatilization

Abstract: The removal of arsenic from drinking water sources produces arsenic-bearing wastes, which are disposed of in a variety of ways. Several disposal options involve anaerobic environments, including mixing arsenic waste with cow dung, landfills, anaerobic digesters, and pond sediments. Though poorly understood, the production of gaseous arsenic species in these environments can be a primary goal (cow dung mixing) or an unintended consequence (anaerobic digesters). Once formed, these gaseous arsenic species are rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…For the strategy of mixing As WTRs with organic waste, the system boundary does not include the organic residues (e.g., cow dung). The fraction of As converted to volatilized species (90%) and the aqueous phase (10%) during disposal was estimated from the available scientific literature. Finally, for open disposal, this strategy was assumed to occur via dumping As WTRs directly into surface waters, consistent with the documented literature. , This system boundary includes the As flows arising from As leaching from the WTRs, which is estimated to be 90% to the aqueous phase and 10% to soils (sediment). , …”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…For the strategy of mixing As WTRs with organic waste, the system boundary does not include the organic residues (e.g., cow dung). The fraction of As converted to volatilized species (90%) and the aqueous phase (10%) during disposal was estimated from the available scientific literature. Finally, for open disposal, this strategy was assumed to occur via dumping As WTRs directly into surface waters, consistent with the documented literature. , This system boundary includes the As flows arising from As leaching from the WTRs, which is estimated to be 90% to the aqueous phase and 10% to soils (sediment). , …”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…The volatilization of As via methylation will in principle lower the As content of contaminated soils, and this is favored under reducing conditions (Frohne et al, 2011). Methanogenic conditions also slightly favor the methylation of As (Webster et al, 2016). Arsenic methylation is widespread in the environment, including in mining environments (Héry et al, 2014;Ngegla et al, 2020).…”
Section: Impact Of Biogeochemical Cyclingmentioning
confidence: 99%
“…MMA was mostly detected in the sample of MP. This may be due to the presence of different As(V)-reducing microorganisms in the biogas slurry that transform As(V) to As(III) under reduction conditions, subsequently converting it to MMA, DMA, and trimethylarsine (TMA), which is released with the methane through As methylation [18]. MMA is the intermediate phase of methylation.…”
Section: Dissolved Fractions Of Asmentioning
confidence: 99%
“…It has been reported that a range of arsine and methyl-arsine species from arsenate were produced by cultures of methanogens [26]. The impact of methanogenesis on As volatilization has been studied in As-bearing ferric iron waste, in which As volatilization represented <0.02% of the total As added [18]. The quantification of genes involved in As biotransformation processes can be taken as an indicator for As transformation.…”
Section: As Species Concentration Vs As Metabolism Gene Copy Numbersmentioning
confidence: 99%